Effect of Blood Pressure Variability During the Acute Period of Subarachnoid Hemorrhage on Functional Outcomes. (18th November 2021) - Ascanio, Luis C; Enriquez-Marulanda, Alejandro; Maragkos, Georgios A; Salem, Mohamed M; Alturki, Abdulrahman Y; Ravindran, Krishnan; Fehnel, Corey R; Hanafy, Khalid; Ogilvy, Christopher S; Thomas, Ajith J; Moore, Justin M
Graphical Abstract: